Peran Kepala Madrasah Dalam Meningkatkan Manajemen Berbasis Madrasah - Mohamad Nur Kholis; Mumun Munawaroh; wahyono wahyono (Oasis : Jurnal Ilmiah Kajian Islam, 2024)
The head of the madrasa has a role in improving the performance of all human resources in the educational institution he leads. The purpose of this study was to determine the profile and role of madrasah principals in improving madrasah-based management, as well as to identify supporting and inhibiting factors in improving madrasah-based management. This study uses qualitative methods with in-depth observation data collection, interviews and documentation. The results showed that the profile of the madrasah principal had met the criteria as stipulated in the Minister of National Education Regulation Number 13 of 2007. The role of the madrasah principal in improving madrasah-based management is good, as an Educator, Manager, Supervisor, Leader, Innovator, and motivators. This madrasa-based management, improvement with curriculum management and program teaching, management of educators and education personnel, student management, financial and financial management, management of facilities and infrastructure, community roles, special service management have also improved and implemented well the indicators that have been determined in each management. Supporting and inhibiting factors in improving madrasa-based management include: madrasas on the main village route, having adequate facilities and infrastructure, the cohesiveness between teachers in supporting all policies made by the madrasa.